HUBUNGAN PENGETAHUAN IBU TENTANG IMUNISASI DASAR DENGAN KELENGKAPAN PEMBERIAN IMUNISASI PADA BAYI - Yopi Wulandhari - (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
Immunization programs in infants expect each baby to get all five basic immunization types.The success of a baby in getting 5 types of basic immunization is measured through a completebasic immunization indicator. Negative impact for children who are not fully immunized is thatthe child may be at risk of contracting or contracting preventable diseases by immunizingtuberculosis, Diphtheria, Polio, and Measles. Full immunization coverage based on healthoffice in Indragiri Hulu district is still found 32.1% immunized but not complete, and 87.1%are never immunized, for various reasons. The purpose of this research is to know therelationship of mother knowledge about basic immunization with completeness of givingimmunization to infant at kampong village of working area of puskesmas kambesko in 2016.The method used is analytical method with Cross Sectional design and sampling technique isTotal Samplin. The result of the research shows that 76 respondents have enough knowledge of42 respondents (55,3%), and from 76 respondent majority give complete immunization as 56person (73,7%). Results by using chi-square obtained p value <0.05 (p = 0.03). Conclusionthere is a relationship of mother knowledge about basic immunization with completeness ofimmunization at baby in village of Kampung Island working area of Puskesmas Kambesko2016.Keywords: Knowledge, basic immunization, completeness of immunization